Comparisons of lanthanide/actinide +2 ions in a tris(aryloxide)arene coordination environment. Issue 11 (18th September 2017) - Fieser, Megan E.; Palumbo, Chad T.; La Pierre, Henry S.; Halter, Dominik P.; Voora, Vamsee K.; Ziller, Joseph W.; Furche, Filipp; Meyer, Karsten; Evans, William J.
Abstract : Nd, like U, prefers a f 4 configuration with the tris(aryloxide)arene ligand rather than the 4f 3 5d 1 configuration found in tris(cyclopentadienyl) complexes. Abstract : A new series of Ln 3+ and Ln 2+ complexes has been synthesized using the tris(aryloxide)arene ligand system, (( Ad, Me ArO)3 mes) 3−, recently used to isolate a complex of U 2+ . The triphenol precursor, ( Ad, Me ArOH)3 mes, reacts with the Ln 3+ amides, Ln(NR2 )3 (R = SiMe3 ), to form a series of [(( Ad, Me ArO)3 mes)Ln] complexes, 1-Ln . Crystallographic characterization was achieved for Ln = Nd, Gd, Dy, and Er. The complexes1-Ln can be reduced with potassium graphite in the presence of 2.2.2-cryptand (crypt) to form highly absorbing solutions with properties consistent with Ln 2+ complexes, [K(crypt)][(( Ad, Me ArO)3 mes)Ln], 2-Ln . The synthesis of the Nd 2+ complex [K(crypt)][(( Ad, Me ArO)3 mes)Nd], 2-Nd, was unambiguously confirmed by X-ray crystallography. In the case of the other lanthanides, crystals were found to contain mixtures of2-Ln co-crystallized with either a Ln 3+ hydride complex, [K(crypt)][(( Ad, Me ArO)3 mes)LnH], 3-Ln, for Ln = Gd, Dy, and Er, or a hydroxide complex, [K(crypt)][(( Ad, Me ArO)3 mes)Ln(OH)], 4-Ln, for Ln = Dy. A Dy 2+ complex with 18-crown-6 as the potassium chelator, [K(18-crown-6)(THF)2 ][(( Ad, Me ArO)3 mes)Dy], 5-Dy, was isolated as a co-crystallized mixture with the Dy 3+ hydride complex, [K(18-crown-6)(THF)2 ][(( Ad, Me ArO)3 mes)DyH], 6-Dy . Structural comparisons of1-Ln and2-Ln are presented with respect to their uranium analogs and correlated with density functional theory calculations on their electronic structures.